Vedic Plaster: The Sustainable Enterprise - Rawat, Prigya (AMC Indian Journal of Entrepreneurship, 2019)
The purpose of this paper was to showcase successful business model based on sustainable resources which have side-lined the conventional route taken by most of the practitioners worldwide. The business model duplication is possible by going through the existing work of an exemplary organization named Vedic Plaster, the Indian sustainable organization led by a bunch of enthusiastic people that created a breakthrough in the cement industry by going organic. In this paper, an honest attempt to practically elaborate the concept of sustainable entrepreneurship was tried. Sadly, till now it has been restricted more to the academicians than practitioners. The current body of work unfolds the story of Dr. Shiv Darshan Malik, a sustainable entrepreneur from India. The USP of the organization is the replacement of cement with plaster formed using Indian breed cow-dung. The case encompasses five stages starting with the introduction, his inspiration, operations, value proposition offered, and challenges faced. The value created by his organization practising sustainability can become the roadmap for other sustainable entrepreneurs willing to start their ventures.